Prenatal observation of nystagmus, cataracts, and brain abnormalities in a case of Zellweger spectrum disorder syndrome. (25th July 2016) - Shen, Ori; Michaelson‐Cohen, Rachel; Gross‐Tsur, Varda; Eilat, Avital; Yanai, Nili; Green, Tamar; Rabinowitz, Ron; Meiner, Vardiella
Abstract : What's Already Known About This Topic? Zellweger syndrome is a severe autosomal recessive disease rarely diagnosed prenatally. What Does This Study Add? This is the first report of nystagmus diagnosed on prenatal ultrasound and the first report on fetal ocular abnormalities associated with Zellweger syndrome.